2021
DOI: 10.3390/ijms22073325
|View full text |Cite
|
Sign up to set email alerts
|

Xyloglucan Oligosaccharides Hydrolysis by Exo-Acting Glycoside Hydrolases from Hyperthermophilic Microorganism Saccharolobus solfataricus

Abstract: In the field of biocatalysis and the development of a bio-based economy, hemicellulases have attracted great interest for various applications in industrial processes. However, the study of the catalytic activity of the lignocellulose-degrading enzymes needs to be improved to achieve the efficient hydrolysis of plant biomasses. In this framework, hemicellulases from hyperthermophilic archaea show interesting features as biocatalysts and provide many advantages in industrial applications thanks to their stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…In addition, we have previously reported that in S. solfataricus the α-xylosidase XylS and the β-glycosidase Ssβ-gly, hydrolyzed tamarind seed xyloglucan oligosaccharides in vitro [48]. More recently, we observed that the α-L-fucosidase is able to remove the fucose residues from fucosylated xyloglucan oligosaccharides [59], suggesting that the three enzymes cooperate for the hydrolysis of xyloglucan oligosaccharides [17] like it has been suggested in T. maritima [49].…”
Section: Discussionsupporting
confidence: 58%
“…In addition, we have previously reported that in S. solfataricus the α-xylosidase XylS and the β-glycosidase Ssβ-gly, hydrolyzed tamarind seed xyloglucan oligosaccharides in vitro [48]. More recently, we observed that the α-L-fucosidase is able to remove the fucose residues from fucosylated xyloglucan oligosaccharides [59], suggesting that the three enzymes cooperate for the hydrolysis of xyloglucan oligosaccharides [17] like it has been suggested in T. maritima [49].…”
Section: Discussionsupporting
confidence: 58%
“…Jonuscheit et al, 2003; Wagner et al, 2012), including promoter investigations (Berkner et al, 2007; 2010; Peng et al, 2012; van der Kolk et al, 2020) or analyses of oligosaccharide hydrolysis (e.g. Curci et al, 2021). In contrast to esterase Saci_1116, LacS exhibits substantial expression levels even without 5’-UTR.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, fucosidases belonging to clusters 2, 3, and 4 have been reported to have promiscuous activities for α1,2/3/4/6 fucosyl linkages (Table S1 ). Fucosidases in clusters 2 and 3 have been reported to release Fuc from xyloglucans 8 , 14 , 34 , 35 . Cluster 2 also contained the newly found exo-α- l -galactosidase BpGH29 from Bacteroides plebeius DSM 17135 36 .…”
Section: Resultsmentioning
confidence: 99%